EFFICACY OF SILVER ZEOLITE ON HEMATOLOGY AND SURVIVAL RATE IN CYPRINUS CARPIO INFECTED WITH SAPROLEGNIA SPP. - Mussab K. Abdulhameed; S. A. Mustafa (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was undertaken to evaluate the effect of silver zeolite (SZ) on hematological parameters and survival rate in common carp, Cyprinus carpio infected with Saprolegnia spp. A total of 120 fish (weight 100 g) were divided into six treated groups in duplicate (10 fish/tank) as follows: T1, T2, T3 and T4 that infected with Saprolegnia spp. (2×104 zoospore/ml) and treated with SZ at (100,200 and 300 mg/l) while T4 infected with Saprolegnia spp. and treated with copper sulfate )5g/100 L(; C+ group, fish were infected with Saprolegnia without treatment and C- served as control negative group. Following 14 days from infection with Saprolegnia spp. and treatment with SZ, considerable changes were observed in blood indices. In pre-treatment, results showed a significant increased (P≤0.05) in WBC count in all infected fish (C+, T1, T2,T3 and T4) in comparison to C- group. RBC, Hb content and PCV% registered a significantly decreased (P≤0.05) in all infected fish (C+,T1, T2,T3 and T4) relative to the control group (C-). Post treatment, WBC registered significantly decreased in treated groups (T1,T2,T3 and T4) compared to C+ in WBC count. The best survival was recorded in T3 (85%) followed by T2 and T1 (65%, and 60%) respectively. In conclusion Silver zeolite seems to be a valuable disinfectant agent against Saprolegnia spp.; at the dose of 300 mg/l.